2006
DOI: 10.1002/ajmg.a.31091
|View full text |Cite
|
Sign up to set email alerts
|

Clinical findings in 33 subjects with large supernumerary marker(15) chromosomes and 3 subjects with triplication of 15q11‐q13

Abstract: We present clinical data on 33 subjects with additional copies of the Prader-Willi-Angelman critical region (PWACR) contained in a supernumerary marker chromosome (SMC). Twenty-three subjects had a typical large non-mosaic SMC(15) containing two copies of the PWACR. They showed a variable but generally severe phenotype of learning disability and autism, with seizures in approximately two-thirds. The other 10 differed from this typical pattern in respect of mosaicism, variation in copy number, or arrangement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 26 publications
(37 reference statements)
2
54
1
1
Order By: Relevance
“…Perhaps the most common CNV in autism are proximal duplications of the long arm of chromosome 15 (15q) due to the presence of low copy repeats, which make this region susceptible to chromosomal rearrangement. 1,2 There are five common breakpoints (BP1-BP5) in the 15q11.2-q13 region, which are at the boundaries of both deletions and duplications of chromosomal regions. Deletions result in either Angelman syndrome (AS) or Prader-Willi syndrome (PWS), depending on the parent-of-origin of the affected allele containing the PWS/AS critical region (PWACR) located between BP2-BP3.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the most common CNV in autism are proximal duplications of the long arm of chromosome 15 (15q) due to the presence of low copy repeats, which make this region susceptible to chromosomal rearrangement. 1,2 There are five common breakpoints (BP1-BP5) in the 15q11.2-q13 region, which are at the boundaries of both deletions and duplications of chromosomal regions. Deletions result in either Angelman syndrome (AS) or Prader-Willi syndrome (PWS), depending on the parent-of-origin of the affected allele containing the PWS/AS critical region (PWACR) located between BP2-BP3.…”
mentioning
confidence: 99%
“…Parent-of-origin gene dosing appears to influence phenotype in idic (15); maternally inherited or derived interstitial duplications are associated with increased autism risk. 1,[10][11][12][13] Idic(15) chromosomes that include the BP2-BP3 region are virtually all maternally derived. Large maternally derived partial hexosomy for 15q11.2-q13 in two boys with intractable epilepsy further suggests that increased dosage of maternally expressed genes negatively impacts the idic(15) phenotype.…”
mentioning
confidence: 99%
“…Indeed, the individuals carrying an sSMC show a wide range of clinical variability, which may be related to the different sizes of the sSMC, the presence and/or absence of euchromatic material, the degree of mosaicism and/or uniparental disomy (UPD) [Liehr et al, 2006]. sSMC have been described from all chromosomes although most of them are derivatives of acrocentric chromosomes [Liehr et al, 2004[Liehr et al, , 2006 and approximately 30% are inherited [Dennis et al, 2006;Liehr and Weise, 2007]. 70% of non-acrocentric sSMC do not have phenotypic consequences, while the remaining 30% show different clinical manifestations [Liehr et al, 2006].…”
mentioning
confidence: 99%
“…Between 1994 and 2008, approximately 160 patients diagnosed with inverted (inv) dup (15) were characterized (Battaglia, 2008;Dennis et al, 2006;Webb, 1994;Webb et al, 1998;Wolpert et al, 2000a, b), and had a similar male:female ratio (3:1) to that reported in idiopathic autism (Bryson, 1996) and in probands with dup (15q) (Wolpert et al, 2000a).…”
Section: Clinical Characteristicsmentioning
confidence: 93%